Information and Communication Technologies for Training in Socioemotional Competencies: An exploratory-descriptive analysis of the main proposals - Ardiles-Briones, M; Segovia-Fernández, A (UNIV SANTIAGO CHILE, FAC TECNOLOGICA, 2025)
Socio-emotional skills have proven to be a protective factor that fosters interpersonal relationships and is used in various everyday situations to respond to new social needs inherent to human beings. These skills are related to a set of competencies distinct from cognitive ones. In this context, the incorporation of Information and Communication Technologies (ICTs), the use of the internet, and virtual platforms appear as a useful and valid tool for training and development in these types of skills. This article aims to analyze the main technological tools fortraining and development in socio-emotional skills, based on an exploratory-descriptive review of recent scientific literature. An exploratory-descriptive study was conducted by searching for articles published between 2023 and 2024 in the SciELO, Redalyc, and Web of Science databases, supplemented by Google Scholar, considering studies in Spanish and English that used digital technologies for the development of socio-emotional skills. The results highlightthattechnologies such as Virtual Reality (VR), Augmented Reality (AR), and Serious Games are the most frequently usedtools in thisfield, mainly in educational and training contexts, both in the general population and in groups with specific needs.